Nuclear Alarmin Cytokines in Inflammation - Lili Jiang; Yijia Shao; Yao Tian; Changsheng Ouyang; Xiaohua Wang (Journal of Immunology Research)
Pathogen-associated molecular patterns (PAMPs) are some nonspecific and highly conserved molecular structures of exogenous specific microbial pathogens, whose products can be recognized by pattern recognition receptor (PRR) on innate immune cells and induce an inflammatory response. Under physiological stress, activated or damaged cells might release some endogenous proteins that can also bind to PRR and cause a harmful aseptic inflammatory response. These endogenous proteins were named damage-associated molecular patterns (DAMPs) or alarmins. Indeed, alarmins can also play a beneficial role in the tissue repair in certain environments. Besides, some alarmin cytokines have been reported to have both nuclear and extracellular effects. This group of proteins includes high-mobility group box-1 protein (HMGB1), interleukin (IL)-33, IL-1α, IL-1F7b, and IL-16. In this article, we review the involvement of nuclear alarmins such as HMGB1, IL-33, and IL-1α under physiological state or stress state and suggest a novel activity of these molecules as central initiators in the development of sterile inflammation.